Clinical and Surgical Evaluation of Sentinel Node Biopsy in Patients with Early-Stage Endometrial Cancer and Atypical Hyperplasia - Pöschke, Patrik; Gass, Paul; Krückel, Annika; Keller, Katharina; Erber, Ramona; Hartmann, Arndt; Beckmann, Matthias W.; Emons, Julius (Geburtshilfe und Frauenheilkunde, 2024)
The medical and surgical treatment of endometrial cancer (EC) is evolving toward a more patient-centered and personalized approach. The role of laparoscopic sentinel node biopsy (SNB) for early-stage EC is unclear, and very few data are available for atypical endometrial hyperplasia (AEH). The present study investigated the effectiveness of SNB combined with laparoscopic hysterectomy in patients with early-stage EC and AEH.This was a retrospective, single-center cohort study for the period from January 2018 to December 2023. A total of 102 patients with atypical hyperplasia (n = 20) and early-stage EC (n = 82) findings on diagnostic curettage underwent pelvic sentinel node biopsy during the final operation.Eleven patients (55%) who had initially been diagnosed with AEH were found to have EC in the final pathology report. No lymph node metastases were detected in patients who had initially been diagnosed with AEH; a 3.6% rate of positive SNBs was found in patients with EC. Changes in tumor grade occurred in 31.3% of the patients and changes in FIGO stage in 33%. Bilateral sentinel node (SN) mapping was successful in 94.1% of the patients. The postoperative outcomes were comparable to those of routine clinical practice without SNB.SNB can be safely offered to patients who have precursor lesions and early-stage EC without notably extending surgical times or increasing postoperative morbidity. This approach can be considered and is safe for patients diagnosed with AEH, but it appears to have a rather small impact on these patients.
Keywords: atypical endometrial hyperplasia; endometrial cancer; sentinel node biopsy; indocyanine green; surgery